2011
DOI: 10.1111/j.1439-0507.2010.01927.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida invasion and influences in smoking patients with multiple oral leucoplakias – a retrospective study

Abstract: Treating patients with multiple oral leucoplakias (MOLs) who smoke is more difficult and complicated than treating those with single oral leucoplakia (SOL). Removing the aetiological factors causing MOL can effectively prevent its recurrence. The aim was to study the infection by and influences of Candida in smoking patients with MOLs. A retrospective study was conducted on 136 smoking patients who had clinicopathological OLs. Among these patients, 73 lesions in 31 patients were MOLs, while 105 patients had SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
15
0
3
Order By: Relevance
“…Epithelial dysplasia, if present, exhibits different degrees of severity. 1,3,8,11 It has been shown that there are differences regarding clinical data when comparing dysplastic and non-dysplastic lesions, mainly in relation to gender, age, anatomical site, alcohol consumption and smoking habits. [11][12][13] Therefore, the aim of this retrospective study was to describe the clinical features observed in dysplastic and non-dysplastic OL lesions in both smokers and non-smokers.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial dysplasia, if present, exhibits different degrees of severity. 1,3,8,11 It has been shown that there are differences regarding clinical data when comparing dysplastic and non-dysplastic lesions, mainly in relation to gender, age, anatomical site, alcohol consumption and smoking habits. [11][12][13] Therefore, the aim of this retrospective study was to describe the clinical features observed in dysplastic and non-dysplastic OL lesions in both smokers and non-smokers.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…2 The etiology of OL is variable, and tobacco has been considered a risk factor in a large number of cases, while alcohol, as an independent risk factor, is still questionable. [2][3][4][5][6][7] The concept of malignant transformation of OL is quite controversial. Studies have indicated that there is a 36% chance of malignant transformation if the lesion exhibits dysplastic features.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the presence of Candida and epithelial dysplasia is higher in multiple oral leukoplakia than in single oral leukoplakia (11). Some studies demonstrated that Candida invasion within the oral mucosa may induce an hyperplastic reaction that is a protective response of the host (12) and have an important association with moderate and severe epithelial dysplasia (13).…”
Section: Discussionmentioning
confidence: 99%
“…Prisutnost gljivice Candida potvrđena je mikrobiološkim metodama i histološkom analizom u većini slučajeva čvoraste leukoplakije (3,5,10), što pokazuje i naš slučaj -pronađena je opsežna kolonija tih gljivica na površini obložnog epitela i Munovi mikroapscesi. Prisutnosti gljivice Candida i epitelne displazije češća je kod multiple oralne leukoplakije negoli u slučaju pojedinačne (11). Neka istraživanja pokazala su da invazija gljivicama Candida kod oralne sluznice može potaknuti hiperplastičnu reakciju kao zaštitni odgovor domaćina (12) i usko je povezana s umjerenom i teš-kom epitelnom displazijom (13).…”
Section: Raspravaunclassified
See 1 more Smart Citation